Adrift in time: the subjective experience of circadian challenge during COVID-19 amongst people with mood disorders. (2nd January 2022) - Kahawage, Piyumi; Crowe, Marie; Gottlieb, John; Swartz, Holly A.; Yatham, Lakshmi N.; Bullock, Ben; Inder, Maree; Porter, Richard; Nierenberg, Andrew A.; Meesters, Ybe; Gordjin, Marijke; Haarman, Bartholomeus C. M.; et al.
ABSTRACT: Social distancing/lockdown policies during the coronavirus (COVID-19) pandemic may alter social rhythms of people through imposition of restrictions on normal daily activities. This may in turn challenge circadian function, particularly in people with mood disorders. Although objective data describing the relationship between circadian disturbances and mood disorders exist, data regarding the subjective experience of circadian challenge is sparse, and its association with mood symptoms is unclear. The present qualitative study was one component of a mixed-methods multi-national project, which took advantage of widespread disruption to daily routines due to Government COVID-related lockdowns during 2020. The Behavior Emotion and Timing during COVID-19 (BEATCOVID) survey study included three open questions generating qualitative data on participants' subjective experience of social disruption due to social distancing/lockdown policies, two of which asked about the barriers and opportunities for stabilizing routines. Responses were coded and analyzed using Thematic Analysis. A total of N = 997 participants responded to at least one of the free-text questions. Four themes were identified: 1) loss of daily timed activities, 2) role of social interaction, 3) altered time perception and 4) disruption to motivation and associated psychological effects. Themes were organized into a provisional heuristic map, generating hypotheses for future research centered on the new concept of 'psychological drift.'